Fuel cell vehicles in Malaysia: a review of current progress, opportunities, and challenges for a sustainable future - Hamed, Ali Mahmoud; Tuan Kamaruddin, Tengku Nordayana Akma (Universiti Teknikal Malaysia Melaka (UTeM), 2026)
Malaysia has recently accelerated efforts to integrate hydrogen-powered transportation into its broader sustainability agenda as part of its net-zero carbon by 2050’s commitment. This review paper is to focus on fuel cell vehicles (FCV) in the Malaysian context. It incorporates the most recent policy frameworks, including the 2023 Hydrogen Economy & Technology Roadmap, and synthesises insights from demonstration projects such as the 2025 Putrajaya mobile hydrogen refueling station and Sarawak’s hydrogen-powered buses and autonomous trams. The review examines current technological progress, infrastructure development, and government-led initiatives, while analysing Malaysia’s policy and regulatory environment in relation to FCV deployment. This review aims to provide valuable insights into the feasibility of FCV in Malaysia and offer strategic recommendations for overcoming existing barriers. The finding shows that while FCV represent a strategic initiave for Malaysia’s decarbonization, it successful adoption requires stronger public–private collaboration, expanded infrastructure, clear regulatory frameworks, and targeted incentives to stimulate demand. By addressing these barriers, Malaysia can leverage hydrogen mobility as a catalyst for sustainable transport and strengthen its position as a regional leader in the hydrogen economy